Applying real options analysis to value the GM-Fiat strategic joint venture. (25th January 2010) - Ionici, Octavian; Small, Kenneth; Kramer, Steve
GM and Fiat entered a strategic joint venture (JV) in 2000 that lasted only five years, but set the stage for the resulting meteoric rise of Fiat, who in 2009 acquired Chrysler to become the second largest automobile producer in Europe. We apply real options analysis to value the strategic alliance between GM and Fiat and show how options, in this case a put option, can be used as currency when strong bargaining power exists. We also highlight some of the problems related to the inherent flexibility embedded in the GM-Fiat agreement. As a result, we suggest the need to create a customised model which mitigates the conflict between the conclusion of strategic analysis and the real option approach. Insights from options-based analyses should improve not only the estimates of asset value, but also the decision-making process. Like an engaged couple that never make it to the altar, correctly pricing the strategic options embedded in a JV contract will save money, time and missed opportunities.